Assessing Region XI's university-based R&D productivity and its effect towards development - Lopez, Mitchiko A.
This study entitled "Assessing Region XI's University -Based R&D Productivity and its Effect Towards' Development" has taken a look at the Research and Development (R&D) productivity of higher education institutions and its effect on development by utilizing the Input-Process-Output-Outcome-Impact analytical framework. Qualitative and quantitative methods of analysis were employed (i.e., desktop research, focus group discussion, case aproach), while the Commission on Higher Education (CHED) Regional Management Information System (RMIS) survey instrument and a supplemental survey was used to collect primary data from the Higher Education Institution/State Universities and Colleges (HEIs/SUCs). Research programs of HEIs do not necessarily address regional development needs, except for HEIs that may be considered as research institutions. Public HEIs shows an average of 34 Productivity Index (PI), higher compared to an average of 7 for private HEIs. Productivity outputs are highly localized to a few HEIs, i.e., UP Min, DMSF, SPC, SPAMAST, DOSCST, and DNSC. Using simple correlation, R&D productivity indicators(i.e., ISI publications, R&D expenditures) have positive correlation with Gross Development Product (GDP). HEIs particular R&D experiences i.e., UP Mindanao's supply chain management program and SPAMAST's sea weeds utilization and value-adding showed development impacts (e.g., increase income, decrease expenses, livelihood, etc.). Impacts are likely felt by stakeholders if R&D programs are aligned with development priorities. Faculty involvement is seen to be a very significant factor affecting R&D productivity based on the Production Function estimates done assuming Cobb Douglas form to evaluate the factors affecting productivity. HEIs does not need to start from zero in improving capacity to engage in highly relevant R&D that are responsive to regional development needs. It has a high ratio of faculty with advance degrees(65%), and 44% of which are already involved in R&D. However, transition for a faculty to perform added function of research is difficult in reality. Their function as faculty is defined by teaching, especially among private HEIs. Therefore, to sustain the gains of HEIs R&D efforts, there is a need for continous upgrading of faculty's research competence by increasing their involvement in research activities.